Application of Tutorials at The School Level - Khairul Nizam bin Zainal Badri (Paedagogie: Jurnal Pendidikan dan studi Islam, 2022)
Education is an ongoing effort to produce human beings who have an awareness of their responsibility to God. In carrying out the mission of education, then the approach used to convey knowledge must take into account the level of effectiveness so that the knowledge reaches students. At a time when many people are passionate about the use of technology in the education system, the most important foundation that should be given attention actually lies in the teaching outcomes where students understand the entire content of teaching. The tutorial approach is said to be very effective in addressing the issue but it is more practiced in institutions of higher learning. Motivated by this statement, this study seeks to examine the tutorial approach conducted at Pusat Pengajian Al-Mansoorah, a private educational institution operating in Selangor. The institution was chosen because the researchers who serve in the institution are interested to know more about the level of effectiveness of the tutorial approach that has been conducted since the beginning of 2020. Using an observation and literature -based research approach, this study found that the tutorial concept provides many benefits to the institution in terms of increasing the diversity of teaching techniques among teachers and building knowledge and skills among students. In other words, the tutorial approach if combined with the normal teaching approach is able to develop the potential of students.